Gluco-incretins regulate beta-cell glucose competence by epigenetic silencing of Fxyd3 expression. - David Vallois (Public Library of Science (PLoS), 2014)
Background/aims Gluco-incretin hormones increase the glucose competence of pancreatic beta-cells by incompletely characterized mechanisms. Methods We searched for genes that were differentially expressed in islets from control and Glp1r-/-; Gipr-/- (dKO) mice, which show reduced glucose competence. Overexpression and knockdown studies; insulin secretion analysis; analysis of gene expression in islets from control and diabetic mice and humans as well as gene methylation and transcriptional analysis were performed. Results Fxyd3 was the most up-regulated gene in glucose incompetent islets from dKO mice. When overexpressed in beta-cells Fxyd3 reduced glucose-induced insulin secretion by acting downstream of plasma membrane depolarization and Ca++ influx. Fxyd3 expression was not acutely regulated by cAMP raising agents in either control or dKO adult islets. Instead, expression of Fxyd3 was controlled by methylation of CpGs present in its proximal promoter region. Increased promoter methylation reduced Fxyd3 transcription as assessed by lower abundance of H3K4me3 at the transcriptional start site and in transcription reporter assays. This epigenetic imprinting was initiated perinatally and fully established in adult islets. Glucose incompetent islets from diabetic mice and humans showed increased expression of Fxyd3 and reduced promoter methylation. Conclusions/interpretation Because gluco-incretin secretion depends on feeding the epigenetic regulation of Fxyd3 expression may link nutrition in early life to establishment of adult beta-cell glucose competence; this epigenetic control is, however, lost in diabetes possibly as a result of gluco-incretin resistance and/or de-differentiation of beta-cells that are associated with the development of type 2 diabetes.